Pendidikan Karakter Sekolah Dasar di Era New Normal - Sumiana; Wahyu Susiloningsih (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This article describes the implementation of primary school character education in the new normal era. Each individual has a different character that characterizes each individual, which is reflected in their attitudes, thoughts and actions. In the world of education, students really need character to form their personal good, honest, wise, responsible and able to respect others. Character education is a conscious and planned effort to teach values, character, morals through habituation with the aim of developing students' abilities to be able to decide good and bad, exemplary in solving problems in society in the future. Implementation of character education which is usually taught through habituation at school must be changed online. This research is a descriptive qualitative research. The subjects in this study were teachers and students of SD Negeri Simomulyo I, Sukomanunggal, Surabaya. The data collection technique used was observation of the implementation of character education. The observation data obtained were then reported descriptively. The results of the research were obtained from observations where the implementation of character education in the New Normal Diera was carried out online. Two of the five character values ​​that cannot be implemented in the new normal era, these character values ​​are mutual cooperation and integrity.